High Throughput Parallel Decoding Method for H.264/AVC CAVLC - Yeo, Donghoon; Shin, Hyunchul (ETRI journal, 2009)
A high throughput parallel decoding method is developed for context‐based adaptive variable length codes. In this paper, several new design ideas are devised and implemented for scalable parallel processing, a reduction in area, and a reduction in power requirements. First, simplified logical operations instead of memory lookups are used for parallel processing. Second, the codes are grouped based on their lengths for efficient logical operation. Third, up to M bits of the input stream can be analyzed simultaneously. For comparison, we designed a logical‐operation‐based parallel decoder for M=8 and a conventional parallel decoder. High‐speed parallel decoding becomes possible with our method. In addition, for similar decoding rates (1.57 codes/cycle for M=8), our new approach uses 46% less chip area than the conventional method.